2018
DOI: 10.1101/359802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutation-driven evolution of Pseudomonas aeruginosa in the presence of either ceftazidime or ceftazidime/avibactam

Abstract: 12Ceftazidime/avibactam is a combination of beta-lactam/beta-lactamases inhibitor, which 13 use is restricted to some clinical cases including cystic fibrosis patients infected with 14 multidrug resistant Pseudomonas aeruginosa, in which mutation is the main driver of 15 resistance. This study aims to predict the mechanisms of mutation-driven resistance that 16 are selected for when P. aeruginosa is challenged with either ceftazidime or 17 ceftazidime/avibactam. For this purpose, P. aeruginosa PA14 was subm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…We identified only one mobile genetic element associated with resistance in three isolates This is supported by the emergence of mutations (in some cases identical) in phylogenetically distant lineages against a backdrop of phenotypic variations in sequential isolates from the same patient. These observations confirm the strong contribution of mutation-driven evolution to the population structure of P. aeruginosa (17).…”
Section: Resistance Due To Horizontal Gene Transfersupporting
confidence: 83%
See 1 more Smart Citation
“…We identified only one mobile genetic element associated with resistance in three isolates This is supported by the emergence of mutations (in some cases identical) in phylogenetically distant lineages against a backdrop of phenotypic variations in sequential isolates from the same patient. These observations confirm the strong contribution of mutation-driven evolution to the population structure of P. aeruginosa (17).…”
Section: Resistance Due To Horizontal Gene Transfersupporting
confidence: 83%
“…Development of multidrug resistance in P. aeruginosa lung isolates from cystic fibrosis patients has been mainly attributed to its ability to adapt to the cystic fibrosis airway microenvironment by multiple genotypic changes, hence the emphasis on intra-patient evolutionary isolate analyses (16). However, its ability to develop mutational resistance in the context of high selective pressure is also well known (17).…”
mentioning
confidence: 99%
“…In a previous study, we observed that P. aeruginosa PA14 populations experimentally evolved in the presence of ceftazidime displayed a robust collateral sensitivity to amikacin (25), as a consequence of selection of large chromosomal deletions upon 1 day of adaptive laboratory evolution (ALE) (25). The chromosomal deletions included hmgA, which encodes an enzyme whose lack of activity leads to the hyperproduction of the brown pigment pyomelanin (26); galU, whose inactivation reduces ceftazidime susceptibility (27); and mexXY, which encodes a multidrug resistance (MDR) efflux pump that contributes to P. aeruginosa intrinsic aminoglycosides resistance (28).…”
Section: Introductionmentioning
confidence: 89%
“…To determine whether chromosomal deletions containing mexXY would be early selected during P. aeruginosa evolution in presence of ceftazidime in the set of mutants mentioned above, as it was the case in the wild-type strain PA14 (25), four biological replicates of each single (nfxB177, parR87, mexZ43, orfN50, and nuoD184) and multiple mutants (MDR6 and MDR12), and the wild-type PA14 strain, were subjected to ALE in presence or absence of ceftazidime (a total of 64 populations) for 3 days. Upon 1 day of experimental evolution, almost every P. aeruginosa population challenged with antibiotic hyperproduced pyomelanin (27 of 32 populations; Fig.…”
Section: Evolutionary Robustness Of First Steps Of P Aeruginosa Ceftmentioning
confidence: 99%
“…These results highlight the fact that the acquisition of resistance to one antibiotic can modify the susceptibility to others, either reducing (cross‐resistance) or increasing (collateral sensitivity) bacterial susceptibility to them. While the analysis of cross‐resistance phenotypes gives clues for avoiding the use of some specific antibiotics when bacteria have acquired resistance to another one, the analysis of the collateral sensitivity networks can help to develop combined or cyclic therapeutic regimes (Podnecky et al, ; Sanz‐Garcia, Hernando‐Amado, & Martinez, ). Indeed, Pseudomonas aeruginosa mutants selected in the presence of carbapenems presented decreased susceptibility to doripenem, meropenem, and imipenem, while their susceptibility to aminoglycosides, fluoroquinolones, and noncarbapenem β‐lactams was higher than that of the parental clinical isolate from which these mutants derive (Harrison, Fowler, Abdalhamid, Selmecki, & Hanson, ).…”
Section: Commentarymentioning
confidence: 99%